The Spot sign and Tranexamic acid On Preventing ICH growth – AUStralasia Trial (STOP‐AUST): Protocol of a phase II randomized, placebo‐controlled, double‐blind, multicenter trial. Issue 4 (26th August 2013) - Meretoja, Atte; Churilov, Leonid; Campbell, Bruce C. V.; Aviv, Richard I.; Yassi, Nawaf; Barras, Christen; Mitchell, Peter; Yan, Bernard; Nandurkar, Harshal; Bladin, Christopher; Wijeratne, Tissa; Spratt, Neil J.; et al.
<x xml:space="preserve">Abstract</x> Rationale No evidence‐based acute therapies exist for intracerebral hemorrhage. Intracerebral hemorrhage growth is an important determinant of patient outcome. Tranexamic acid is known to reduce hemorrhage in other conditions. Aim The study aims to test the hypothesis that intracerebral hemorrhage patients selected with computed tomography angiography contrast extravasation 'spot sign' will have lower rates of hematoma growth when treated with intravenous tranexamic acid within 4·5‐hours of stroke onset compared with placebo. Design The Spot sign and Tranexamic acid On Preventing ICH growth – AUStralasia Trial is a multicenter, prospective, 1:1 randomized, double‐blind, placebo‐controlled, investigator‐initiated, academic Phase II trial. Intracerebral hemorrhage patients fulfilling clinical criteria (e.g. Glasgow Coma Scale >7, intracerebral hemorrhage volume <70 ml, no identified secondary cause of intracerebral hemorrhage, no thrombotic events within the previous 12 months, no planned surgery) and demonstrating contrast extravasation on computed tomography angiography will receive either intravenous tranexamic acid 1 g 10‐min bolus followed by 1 g eight‐hour infusion or placebo. A second computed tomography will be performed at 24 ± 3 hours to evaluate intracerebral hemorrhage growth and patients followed up for three‐months. Study outcomes The primary outcome measure is presence of intracerebral hemorrhage growth by 24 ± 3 hours, defined as either >33% or >6 ml increase from baseline, and will be adjusted for baseline intracerebral hemorrhage volume. Secondary outcome measures include growth as a continuous measure, thromboembolic events, and the three‐month modified Rankin Scale score. Discussion This is the first trial to evaluate the efficacy of tranexamic acid in intracerebral hemorrhage patients selected based on an imaging biomarker of high likelihood of hematoma growth. The trial is registered as NCT01702636.